A Century of Recorded Music: Listening to Musical History - Day, Timothy (New Haven, CT Yale University Press, 2000)
This engaging book is the first thorough exploration of the impact of recording technology on the art of music. Timothy Day chronicles the developments in recording technology since its inception and describes the powerful effects it has had on artistic performance, audience participation, and listening habits. He offers a fascinating comparison of the characteristics of musical life a century ago with those of today.
Keywords: 20th Century (1901-2000); Sound recording industry; Music history